Prospects of Applying Enhanced Semi-Empirical QM Methods for 2101 Virtual Drug Design - Duygu Yilmazer, Nusret; Korth, Martin (Current Medicinal Chemistry, 2016)
The last five years have seen a renaissance of semiempirical quantum mechanical (SQM) methods in the field of virtual drug design, largely due to the increased accuracy of so-called enhanced SQM approaches. These methods make use of additional terms for treating dispersion (D) and hydrogen bond (H) interactions with an accuracy comparable to dispersion-corrected density functional theory (DFT-D). DFT-D in turn was shown to provide an accuracy comparable to the most sophisticated QM approaches when it comes to non-covalent intermolecular forces, which usually dominate the protein/ligand interactions that are central to virtual drug design. Enhanced SQM methods thus offer a very promising way to improve upon the current state of the art in the field of virtual drug design.
Keywords: Computational chemistry